A Preliminary Results of Site-Specific Ground Response Analysis of Banda Aceh, Indonesia - Bambang Setiawan; Taufiq Saidi (Syiah Kuala University, 2012)
The Mexico City experience in 1985 demonstrated the importance of siteresponse effects. The site response effect i.e. soil amplification has caused major structure damages founded on thick soft soils. Banda Aceh, Indonesia founded on a formation which can be, typically, similar with the Mexico City. The city is underlain by approximately 70m to 206m thick alluvium. Thus, site-specific ground response analysis is necessary to be carried out to establish the most influential parameter i.e. peak ground acceleration and the spectral fundamental frequency. This ground response analysis was carried out usingcomputer program which is EERA. This analytical analysis has proven able to depict seismic wave behaviour in soft local soil deposits The results of the site-specific ground response studies are expose the real Banda Aceh‟s soil response during the 2004 Sumatran mega earthquake. Peak ground acceleration at soil site, the response spectra and fundamental frequency of the maximum response spectra are presented.